Social Representations of Cancer "Sociological and Analytical Study" - دلالة ميرنا (Tishreen University Journal- Arts and Humanities Sciences Series, 2020)
This research paper relates to a serious disease, the prevalence of which has become apparent, and no one can ignore it, Despite the recent developments reached by doctors and scientists in various fields, whether medical or scientific; however, science remains powerless in front of this disease, whether by finding a cure for it or preventing it or ensuring and determining the reasons for its emergence, They are very complex, intertwined and multiple. Consequently, it remains deficient in achieving complete recovery, except in a few cases when diagnosis and treatment are early. It is cancer. Therefore, the current research problem focuses on knowing the social perceptions of cancer in people with it, We adopted the descriptive and analytical approach to obtain data from a sample of (12) affected individuals.